Beginning biochemistry : A sentinel book - Berman, Willam (New York : Arco Publishing Company, 1977)
The changing world.--Atoms and biochemistry.--The sean within us.--Living mines-minerals and life.--Carbon: a social atoms. prelude to carbohydrate.--The chemistry of carbohydrates.--Biology of carbohydrates.--faleful fats: lipids and related compounds.--Proteins and nucleie acids- the ruling molecules of life.
Incluye índice
Keywords: Bioquimica